The Effect of Microwave Power in the Green Synthesis of Silver Nanoparticles Using Citrus sinensis Peels Extract - Tanty Fatikasari; Iis Nurhasanah; Ali Khumaeni (Jurnal Kimia Sains dan Aplikasi, 2023)
There are numerous green methods for synthesizing silver nanoparticles using plant extracts such as leaves, flowers, stems, and fruit extracts. However, most of those synthesized have weaknesses such as slow reduction and inefficient time. This study used a microwave to accelerate the reduction process of Ag+ ions into Ag0 nanoparticles using an aqueous extract of Citrus sinensis peels. A heating time of 5 minutes produces silver nanoparticles in optimal condition with a color change from yellow to reddish brown. According to UV-Vis, silver nanoparticles at power 100 W and 300 W show peaks at 404 nm and 406 nm. FTIR indicates that phytochemical compounds are involved in the reduction of nanoparticles. XRD shows silver nanoparticles are FCC crystalline. TEM reveals that power 100 W yields an average diameter of 12 nm while 300 W shows a smaller diameter of 5 nm.